New Generation of Muslims in Japan: The “Young Muslim” Community as a New Collective Identity and Space for Mutual Solidarity - Yo Nonaka (Al-Jami'ah: Journal of Islamic Studies, 2026)
Historically, research on Muslims in Japan has been focused on first-generation immigrants and their mosque-centered activities. However, youths socialized within the Japanese education system often experience alienation from existing mosque communities, which they perceive as culturally and linguistically tethered to their parents’ nations of origin. Consequently, these actors have moved beyond labels such as “second-generation Pakistanis” or “converts” to forge a collective “Young Muslim” identity and a space for collaborative action. This paper examines the emergence of “Young Muslims” in Japan—a burgeoning demographic consisting of second-generation individuals and Japanese converts. Based on interviews, participant observation, and collaborative video projects, the research clarifies the motivations behind this self-identified category and the distinct characteristics of their community activities. Unlike the first generation, Young Muslims prioritize digital spaces and informal gatherings, intentionally avoiding doctrinal rigor or mutual religious surveillance. They primarily use Japanese to foster internal solidarity and engage non-Muslim society, seeking to dismantle domestic stereotypes. By developing their own networks and outreach, these youths are constructing a localized, Japanese-speaking public sphere. Ultimately, this movement represents a significant, yet previously overlooked, transformative trend within the contemporary landscape of Islam in Japan. [Secara historis, kajian mengenai Muslim di Jepang lebih banyak berfokus pada imigran generasi pertama dan aktivitas mereka yang berpusat di masjid. Namun, kaum muda Muslim yang tersosialisasi dalam sistem pendidikan Jepang sering kali mengalami keterasingan dari komunitas masjid yang ada, yang mereka pandang masih terikat secara budaya dan linguistik dengan negara asal orang tua mereka. Akibatnya, para aktor ini melampaui label seperti “generasi kedua Pakistan” atau “mualaf” untuk membangun identitas kolektif sebagai “Young Muslims” serta menciptakan ruang bagi aksi dan kolaborasi bersama. Artikel ini mengkaji kemunculan “Young Muslims” di Jepang, yaitu kelompok demografis yang terus berkembang dan terdiri atas Muslim generasi kedua serta mualaf Jepang. Berdasarkan wawancara, observasi partisipatif, dan proyek video kolaboratif, penelitian ini menjelaskan motivasi di balik munculnya kategori identitas tersebut serta karakteristik khas aktivitas komunitas mereka. Berbeda dengan generasi pertama, Young Muslims lebih mengutamakan ruang digital dan pertemuan informal, serta secara sengaja menghindari kekakuan doktrinal maupun pengawasan religius antaranggota. Mereka utamanya menggunakan bahasa Jepang untuk memperkuat solidaritas internal sekaligus berinteraksi dengan masyarakat non-Muslim, dengan tujuan menghapus stereotip yang berkembang di dalam negeri. Melalui pengembangan jaringan dan kegiatan sosialisasi mereka sendiri, kelompok muda ini tengah membangun ruang publik berbahasa Jepang yang berakar pada pengalaman Muslim lokal. Pada akhirnya, gerakan ini merepresentasikan suatu tren transformasi penting yang selama ini kurang mendapat perhatian dalam lanskap Islam kontemporer di Jepang.]